A radial head prosthesis appears to be unnecessary in Mason-IV fracture dislocation. (4th May 2017) - Nestorson, Jens; Josefsson, Per-Olof; Adolfsson, Lars
Abstract : Background and purpose — Previous reports on elbow injuries with concomitant comminute radial head fracture are difficult to interpret, since they include an array of different soft-tissue and bony injuries around the elbow. We focused on Mason-IV fracture dislocations of the elbow and retrospectively reviewed 2 treatment options: radial head resection or replacement with a radial head arthroplasty, both in combination with lateral ligament repair. Patients and methods — In Linköping, 18 consecutive patients with Mason-IV fracture dislocation and with a median age of 56 (19–79) years were treated with a radial head arthroplasty. In Malmö, 14 consecutive patients with a median age of 50 (29–70) years were treated for the same injury with radial head resection. With a follow-up of at least 2 years (Linköping: median 58 months; Malmö: median 108 months), the outcome was assessed using the Mayo elbow performance score (MEPS), the Disabilities of Arm, Shoulder, and Hand questionnaire (DASH), range of movement, instability, and plain radiographs. Results — There was no statistically significant difference between the groups regarding MEPS, DASH, or range of motion. The rate of additional surgery was higher in patients treated with arthroplasty. Ulno-humeral osteoarthritis was more pronounced in the group treated with radial head resection, but the follow-up time was longer in these patients. Functional results and range of motion tally well with previous reports on similar injuries. Interpretation — Functional results did not improve by using a press-fit radial head arthroplasty in Mason-IV fracture dislocation of the elbow. Secondary osteoarthritis after resection of the radial head is a concern, but it did not affect the functional outcome during the follow-up time.